Odpowiedzi

2010-02-04T18:14:53+01:00
1. 6 - ( 1/3 x - 2 ) = 1/3 + 5

6-1/3x+12=1/3+5
-1/3x=1/3+5-12-6
-1/3x=-38/3
x=38

2. 2x - 2 ( 6 - x ) = 0,3 + 0,5 x
2x-12+2x=0,3+0,5x
2x+2x-0,5x=0,3+12
4,5x=12,3
x=123/10:45/10
x=123/10*10/45
x=123/45
1 1 1
Najlepsza Odpowiedź!
2010-02-04T18:15:05+01:00
1.
6 - ( 1/3 x - 2 ) = 1/3 + 5 /×3
18-3(1/3x-2)=1+15
18-x+6=16
18-16+6=x
x=8

2.
2x - 2 ( 6 - x ) = 0,3 + 0,5 x
4x-5/10x=3/10+12
35/10x=123/10 /×10
35x=123 /:35
x=123/35
x=3,51

domi w zadaniu 1 zamiast +2 napisała +12 i przez to ma błąd